Genetic and transcriptome analyses reveal the candidate genes and pathways involved in the inactive shade-avoidance response enabling high-density planting of soybean - Zhao, Jing; Shi, Xiaolei; Chen, Lei; Chen, Qiang; Tian, Xuan; Ai, Lijuan; Zhao, Hongtao; Yang, Chunyan; Yan, Long; Zhang, Mengchen (Frontiers in Plant Science, 2022)
High-density planting is a major way to improve crop yields. However, shade-avoidance syndrome (SAS) is a major factor limiting increased planting density. First Green Revolution addressed grass lodging problem by using dwarf /semi-dwarf genes. However, it is not suitable for soybean, which bear seeds on stalk and whose seed yield depends on plant height. Hence, mining shade-tolerant germplasms and elucidating the underlying mechanism could provide meaningful resources and information for high-yield breeding. Here, we report a high-plant density-tolerant soybean cultivar, JiDou 17, which exhibited an inactive SAS (iSAS) phenotype under high-plant density or low-light conditions at the seedling stage. A QTL mapping analysis using a recombinant inbred line (RIL) population showed that this iSAS phenotype is related to a major QTL, named shade-avoidance response 1 (qSAR1), which was detected. The mapping region was narrowed by a haplotype analysis into a 554 kb interval harboring 44 genes, including 4 known to be key regulators of the SAS network and 4 with a variance response to low-light conditions between near isogenic line (NIL) stems. Via RNA-seq, we identified iSAS-specific genes based on one pair of near isogenic lines (NILs) and their parents. The iSAS-specific genes expressed in the stems were significantly enriched in the ‘proteasomal protein catabolic’ process and the proteasome pathway, which were recently suggested to promote the shade-avoidance response by enhancing PIF7 stability. Most iSAS-specific proteasome-related genes were downregulated under low-light conditions. The expression of genes related to ABA, CK, and GA significantly varied between the low- and normal-light conditions. This finding is meaningful for the cloning of genes that harbor beneficial variation(s) conferring the iSAS phenotype fixed in domestication and breeding practice.